Use of Rubidium to Label Lysiphlebus testaceipes (Hymenoptera: Braconidae), a Parasitoid of Greenbugs (Homoptera: Aphididae), for Dispersal Studies - Fernandes, Odair A. [UNESP]; Wright, Robert J.; Baumgarten, Karl H.; Mayo, Z. B. (My University, 1997)
A reliable method of labeling is needed to study dispersal of the braconid parasitoid, Lysiphlebus testaceipes (Cresson), an important biological control of greenbugs, Schizaphis graminum (Rondani), on grain sorghum, Sorghum bicolor (L.) Moench. The feasibility of using aqueous solutions of rubidium chloride (RbCl) applied as a foliar spray or soil drench to label greenbugs and L. testaceipes developing within greenbugs was studied. Laboratory and field studies were conducted to identify the minimal concentration of RbCl to assure labeling of greenbugs and wasps, persistence of Rb throughout the wasp's life span, mobility of Rb to unsprayed sorghum leaves, and feasibility of studying dispersal using a release-recapture technique with Rb-labeled wasps. Both greenbugs and wasps could be labeled using RbCl at concentrations of 2,500-10,000 ppm. Rubidium content in labeled wasps did not significantly vary during the first 7 d after emergence. Greenbugs feeding on unsprayed leaves were labeled up to 4 wk after leaves were sprayed. Rb-labeled wasps were found at the maximum trap distance from the release site (60 m) within 1 d after release.
Keywords: Dispersal; Grain sorghum; Greenbugs; Lysiphlebus testaceipes; Parasitoids; Rubidium chloride